Specific Aspects of Unregistered Unemployment in the Western Part of Romania - Remeș, Eugen; Schebesch, Klaus Bruno; Remeș, Cosmina; Deac, Dan (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The paper aims at highlighting a current phenomenon on the labour market in Romania, related to the existence of important categories of unemployed persons and looking for a job, but not registered in the statistics of state institutions dealing with unemployment. The analysis is conducted in the area of western Romania (for the Arad, Bihor and Timis counties) and aims categories of unemployed people with different skill levels, which for different reasons, are not accounted for statistically.